Defining the Academic Field of Interreligious Studies - Gustafson, Hans (Interreligious Studies and Intercultural Theology, 2020)
The emergence of Interreligious Studies (IRS) as a recognized academic field is relatively recent, despite several decades if not centuries of scholars engaging in research, teaching, and activism that today could fall under IRS. The past decade has spawned significant scholarly attempts to define IRS and has produced academic programs, conferences, journals, and associations devoted to it. This article collates recent attempts to define IRS by identifying common family resemblances among them, especially insofar as IRS remains distinct from other academic fields, and inquires about major attempts to define the field by identifying a common thread, if there is one, that runs through all attempts. Significant boundaries of IRS are delineated, especially in relation to other approaches to the study of religion (e.g., religious studies and theological studies). In so doing, this article identifies four common characteristics of IRS; it is a) descriptive, b) normative and prescriptive, c) self-implicating, and d) multi-, inter-, and trans-disciplinary.